2015
DOI: 10.1007/s10126-015-9653-9
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Characterization of Eriphia verrucosa Hemocyanin

Abstract: Arthropod hemocyanins (Hcs) are a family of large extracellular oxygen-transporting proteins with high molecular mass and hexameric or multi-hexameric molecular assembly. This study reports for the first time the isolation and characterization of the structure of an arthropod hemocyanin from crab Eriphia verrucosa (EvH) living in the Black Sea. Its oligomeric quaternary structure is based on different arrangements of a basic 6 × 75 kDa hexameric unit, and four of them (EvH1, EvH2, EvH3, and EvH4) were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…In our preliminary study, we have identified a high identity (65%) between EvH and CaeSS2 of C. aestuarii (P 84293.1). These values are very close to the homology reported between the subunits of other hemocyanins and we have suggested that this fragment belongs to EvH4 or EvHc5 [54]. The isolated here Hc subunit of E. verrucosa showed high sequence identity (>60%) with hemocyanins from organisms belonging to the class Malacostraca: Decapoda, Amphipoda, and Isopoda.…”
Section: Isolation Structural and Functional Properties Of E Verrusupporting
confidence: 87%
See 1 more Smart Citation
“…In our preliminary study, we have identified a high identity (65%) between EvH and CaeSS2 of C. aestuarii (P 84293.1). These values are very close to the homology reported between the subunits of other hemocyanins and we have suggested that this fragment belongs to EvH4 or EvHc5 [54]. The isolated here Hc subunit of E. verrucosa showed high sequence identity (>60%) with hemocyanins from organisms belonging to the class Malacostraca: Decapoda, Amphipoda, and Isopoda.…”
Section: Isolation Structural and Functional Properties Of E Verrusupporting
confidence: 87%
“…Glycosylation is frequently observed in crustacean hemocyanins [27,[50][51][52][53]. The native hemocyanin isolated from E. verrucosa is glycosylated but the concentration of monosaccharides is very low [54]. To determine the position of potential glycosylated sites of EvHc5, a 3D-model was performed, which showed the glycosylated sites exposed on the surface of the subunit at the same place as in P. interruptus (Figure 5).…”
Section: Glycosylation Sites In the E Verrucosa Hemocyanin Subunitmentioning
confidence: 99%
“…A 2 x 6-meric hemocyanin nearly identical to hemocyanin found in decapod crustaceans has been studied from springtail taxa (Collembola) (Schmidt et al, 2019). Further, 6 x 75 kDa hexameric unit oligomeric quaternary structure has been refined for hemocyanin from crab Eriphia verrucosa (Dolashki et al, 2015). As understood from the sequence-level features and domain analysis of Mr_HC_1, the hemocyanin_N is all alpha domains in all chains with beta-fold recognized in the hemocyanin_M and hemocyanin_C domains.…”
Section: Resultsmentioning
confidence: 99%
“…Further investigations are necessary to determine the complete sequence of subunit ScuHc2 and to answer this question. For example, the complete amino acid sequence and the glycosylation of the hemocyanins from the malacostracean taxa Carcinus aestuarii and Eriphia verrucosa helped to understand the quaternary structure of the molecules [31,32]. These analyses could also help to gain a better understanding of the quaternary structure of hexapod hemocyanins.…”
Section: Resultsmentioning
confidence: 99%